Birth weight and bone mass in young adults from Brazil. - Schlüssel, M; de Castro, J; Kac, G; da Silva, A; Cardoso, VC; Bettiol, H; Barbieri, M (2010)
BACKGROUND: Birth weight is positively associated with adult bone mass. However, it is not clear if its effect is already evident in early adulthood. OBJECTIVE: To investigate the association between birth weight, adult body size, the interaction between them and bone mass in young adults. METHODS: Bone densitometry by DXA was performed on 496 individuals (240 men) aged 23-24 years from the 1978/79 Ribeirão Preto (southern Brazil) birth cohort, who were born and still residing in the city in 2002. Birth weight and length as well as adult weight and height were directly measured and converted to z-scores. The influence of birth weight and length, and adult weight and height on bone area (BA), bone mineral content (BMC) and bone mineral density (BMD) at the lumbar spine, proximal femur and femoral neck were investigated through simple and multiple linear regression models. Adjustments were made for sex, skin color, gestational age, physical activity level, smoking status and dietary consumption of protein, calcium and alcohol. Interaction terms between birth weight and adult weight, and birth length and adult height were tested. RESULTS: Men in the highest tertile of birth weight distribution had greater BA and BMC at all three bone sites when compared with their counterparts in the lowest tertiles (p<0.008). For BMD, this trend was observed only in the lumbar spine. Adult weight and height were positively associated with BA and BMC at all three bone sites (p<0.05). For BMD, these associations were seen for adult weight, but for adult height an association was observed only in the lumbar spine. Birth weight retained positive associations with proximal femur BA and BMC after adjustments for current weight and height. No interaction was observed between variables measuring prenatal growth and adult body size. CONCLUSION: Birth weight and postnatal growth are independent determinants of adult bone mass in a sample of Brazilian adults. This effect is already evident in early adulthood.